TELESIMULATION AS A REMOTE TEACHING METHOD FOR CARIOPULMONARY RESUSCITATION: EXPERIENCE REPORT - Azeredo, Giselle Oliveira; Silva, Renata Flavia Abreu da; Nunciaroni, Andressa Teoli; Ferreira, Caroliny Suhet Xavier; Corrêa, Vanessa de Almeida Ferreira (Cogitare Enfermagem, 2023)
Objective: to describe the experience in the elaboration and implementation of a remote course on Cardiopulmonary Resuscitation for health professionals by means of Telesimulation. Development: an experience report about a course for Cardiopulmonary Resuscitation training, developed remotely and synchronously with 227 health professionals between June and July 2021 in the state of Rio de Janeiro - Brazil. The course was taught for 35 groups of students by applying the following: pre-test, video class and post-test 1; and Telesimulation and post-test 2 with perception assessment. In the assessment, Telesimulation stood out as a motivation strategy for improved learning about the topic, evidenced by the increase in the number of correct answers between the tests. Conclusion: the participants showed interest in the course, which proved to be a learning strategy, also considered as an innovation possibility for permanent education in health.